Consumption behavior and the lack of financial literacy among teens - Sifa Asri Trisnani; Atika Dian Adriyani; Rifky Aulia Wandansari; Wikan Isthika (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2019)
Purpose – The main purpose of this study is to examine role of financial literacy, peer conformity, and hedonic lifestyle towards teenagers’ consumption behavior.Method - Consumer behavior explains the desire to have excessive consumption. The population in this study were all adolescents high school and university in the region of Central Semarang, amounting to 26 583 students, with a sample of 100 adolescents. This study uses a quantitative approach to data collection methods in the form of a questionnaire. The analytical method used is multiple linear regression analysis.Result - Peer conformity, hedonistic lifestyle, and financial literacy simultaneously influence consumer behavior adolescent high school and university in the Middle Semarang with a contribution of 37%. Partially significance value 0769 for peer conformity and 0. 992 for financial literacy while lifestyle 0:00 hedonic significance value. In this study, only hedonic factors that influence consumer behavior of teenagers.Implication - This study can be used to understand behavior in teenager, especially in terms of purchase and consumption behavior.Originaility - This research examine financial literacy in teenager phase.